As políticas econômicas constitucionais como fator de legitimidade das decisões do conselho administrativo de defesa econômica - CADE - Arthur Villamil Martins (2013)
This thesis has as its central proposition to demonstrate that the combination of technical economic and political criteria, through a technical-political-legal balance can increase the degree of legitimacy of decisions of Conselho Administrativo de Defesa Econômica (Cade). Based on the historical and theoretical analysis of Antitrust Law, through an analysis of theories of efficiency and economy and for verifying the treatment of the theme in comparative Law, with concrete cases judged by the European Commission and by Cade, the work seeks clarify how the consideration of constitutional economic policies by Cade can function as a mechanism for implementing the constitutional economic order, with maximization of social wealth, trying to assure everyone the dignity of the human person, which is the ultimate goal of all economic constitutional order.